Risk of myocardial infarction and heart failure in gout patients: a systematic review and meta-analysis - Panpan Wang; Huanhuan Yang (Journal of Cardiothoracic Surgery)
Abstract Background Gout is a metabolic disease caused by decreased blood uric acid excretion and purine metabolism disorders. Long-term and persistent metabolic dysfunction gradually affects other organ functions and is the main factor inducing Myocardial Infarction (MI) and Heart Failure (HF), seriously affecting the health of patients. This study adopts a meta-analysis to analyze the risk of MI and HF in gout patients. Methods Clinical research literature related to gout complicated with MI or HF was searched in databases such as PubMed, Embase, Web of Science, Cochrane Library, etc. through computer retrieval before March 2023. Literature content was carefully read and retrieved, and screening was conducted based on inclusion and exclusion criteria. Relevant data were extracted from the final screened literature, and a forest map was drawn using RevMan 5.3 software for meta-analysis. Results After searching in various databases, 2519 articles were obtained. After screening, 8 articles were finally included for meta-analysis. Among the 22 included literature, 9 analyzed the risk of gout and MI, and heterogeneity tests showed P = 0.20 and I 2  = 28%. Fixing effects analysis showed RR = 4.60, 95%CI = 4.39–4.82, and P < 0.001. Nine articles analyzed the risk of gout and HF, and heterogeneity tests showed that P = 0.13 and I 2  = 37%. Fixing effects analysis showed RR = 2.71, 95%CI = 2.61–2.82, and P < 0.001. Eight studies compared the incidence of MI or HF between male gout and non-gout patients. Heterogeneity tests showed P = 0.21 and I 2  = 28%, while fixing effects analysis showed RR = 1.98 and 95%CI = 1.89–2.01, with P < 0.001. Four articles statistically compared the incidence of MI or HF between female gout and non-gout patients. Heterogeneity tests showed P = 0.15 and I 2  = 43%. Fixing effects analysis showed RR = 1.70, 95%CI = 1.57–1.83, and P < 0.001. Thirteen studies compared the incidence of MI or HF in gout patients of different genders. Heterogeneity tests showed P = 0.37 and I 2  = 7%. Fixing effects analysis showed RR = 0.03, 95%CI = 0.03–0.03, and P < 0.001. Conclusion Compared to non-gout patients, gout patients are more prone to MI or HF and are not affected by gender. However, among gout patients, women have a higher risk of MI or HF than men.